Freshwater diatoms of the Ecology Glacier foreland, King George Island, South Shetland Islands - Natalia Kochman-Kędziora; Teresa Noga; Maria Olech; Bart Van De Vijver (Polish Polar Research, 2018)
Diatom assemblages from small pools and creeks on the Ecology Glacier forefield have been investigated. It is the first study in the Admiralty Bay region after the thorough taxonomic revision of the non-marine Antarctic diatom flora. A total of 122 diatom taxa, belonging to 35 genera were identified. More than 55% of all observed species have a restricted Antarctic distribution. Another 15% have a marine origin. Nitzschia gracilis Hantzsch, N. homburgiensis Lange-Bertalot and Planothidium rostrolanceolatum Van de Vijver et al. dominated the flora. Based on a DCA analysis, samples were subdivided in three groups reflecting ecological differences. Several samples (group 1) showed a mixed freshwater/marine diatom composition and are typical for coastal pools. Two other groups were separated based on the amount of limnoterrestrial taxa indicating the temporary character of some of the pools.